Impacto de la vigilancia tecnológica en las pymes de la industria alimentaria - Mejía Chávez, Araceli Olivia (2024)
Small and medium-sized enterprises (SMEs) in the food industry of the Mexico City Metropolitan Area (MCMA) utilize technology watch for the systematic collection and analysis of information from various sources. This generates knowledge through market research, competitor analysis, and technological trend identification, among others, which enables companies to make informed decisions. Technology watch is one of the five functions that comprise the management model of the Mexican National Technology and Innovation Award, which also includes planning, enablement, protection, and implementation. The objective of this research is to analyze the technology watch activities and practices carried out by food SMEs in the region, and based on this, to understand the impact of technology watch on these companies. This study conducted direct research through surveys applied to food SMEs and desk research on the topic. The research concludes that technology watch has contributed to solving market needs, identifying technological development projects, and improving strategic and technological planning in this type of company.